Futuristic restoration: an oxymoronic paradigm for an idiosyncratic place in time. Issue 6 (19th October 2020) - Pape, Timothy
Abstract : Restoration ecology has grown in political prominence in the past decades with the United Nations General Assembly's declaration of 2021–2030 the "UN Decade on Ecosystem Restoration" representing a highly visible vindication for the discipline. That said, questions of environmental justice, economic practicality, and ethics need to be considered when climate change and environmental degradation are factored into restoration projects. This article builds on previous calls for a paradigm of ecological restoration which looks toward the future, and not the past. Future‐oriented restoration projects should: (1) examine how restored ecosystems will affect local and disadvantaged communities; (2) assess whether the restoration goals will improve human health and safety; (3) evaluate how financially feasible the goals are from a systems perspective; and (4) strive for transparency of the values that inform such projects. The concept of sustainability and how it applies to restoration ecology will also be discussed.